Comparison of six different calprotectin assays for the assessment of inflammatory bowel disease. Issue 1 (February 2014) - Labaere, Delphine; Smismans, Annick; Van Olmen, August; Christiaens, Paul; D'Haens, Geert; Moons, Veerle; Cuyle, Pieter-Jan; Frans, Johan; Bossuyt, Peter
Background and objectives: Faecal calprotectin is a valuable noninvasive marker for inflammatory bowel disease (IBD). The aim of our study was to determine the correlation between six different calprotectin assays and compare their performance for diagnosis and follow up of IBD. Methods: Thirty-one patients with suspected IBD and 31 patients in follow up were included. We determined calprotectin by means of three rapid immmunochromatographic tests, two enzyme-linked immunosorbent assays, and one automated fluoroimmunoassay. Results were correlated with endoscopic and histological findings. Results: Although all methods correlated significantly, slopes and intercepts differed extensively, with up to 5-fold quantitative differences between assays. Sensitivity and specificity for diagnosis of IBD were 82–83 and 84–89%, respectively. For follow up, sensitivity in detecting mild ulcerative colitis was 71–100%. In moderate-to-severe ulcerative colitis, sensitivity was 100% for all assays. Specificity was 67–86% in both subgroups. In Crohn's disease, only moderate-to-severe disease could be differentiated from remission, with sensitivity 83–86% and specificity 75% for all tests. Conclusions: All calprotectin assays showed comparable clinical performance for diagnosis of IBD. For follow up, performance was acceptable, except for mild Crohn's disease. Because of the large quantitative differences, further efforts are needed to standardize calprotectin assays.